PEMAKSIMALAN FUNGSI UTAMA RETAILING ALFAMART MINI MARKET DI BANDAR LAMPUNG - -, Herlina (Jurnal Manajemen dan Keuangan, 2010)
Retail is an industry based on customers that depend on how to realize what is needed and needed consumer. The purpose of this study is to determine whether there is a positive and significant effect of maximizing the main functions of retailing and is the most dominant factor of maximizing the main functions of retailing. The test results can influence the outcome acount availability of goods sold (X1) of greater than table 3.404 (1.662) means, the results obtained by the availability of goods sold (X1) has a positive and significant influence on the maximization of retailing (Y). acount location (X2) was smaller than table 1.232 (1.662) means, the results obtained by the location (X2) does not affect positively towards maximizing retailing. acount price (X3) of 3.328 which is greater than table (1.662) means, the results obtained by the price (X3) affects positively to maximize retailing. acount promotion (X4) of 1.793 which is greater than table (1.662) means, the results obtained promotion (X4) affects positively to maximize retailing. acount service shop (X5) of -0.437 which is smaller than table (1.662) means, the results obtained by the service shop (X5) does not affect positively towards maximizing retailing.Keywords: Retailing, availability of goods sold, Location, Price, Service Shops, maximizing Retailing.